(untitled) (Entrepreneurship Journal for Finance and Business, 2023)
The research tracks the problem of the high level of poverty in the country and the relationship of private commercial banks and their work to reduce this problem with the lack of effective solutions and initiatives to reduce this problem, especially since the contribution of these banks in solving this problem is limited. Therefore, the research will track the contribution of these banks to reduce poverty by developing their role And increasing the financing role, on the basis that commercial banks are a basic starting point for increasing bank financing in order to increase the establishment of small and medium enterprises, increase production capacity and contribute to the process of economic and social development, as commercial banks of all kinds are important tools of the economic system in the modern era and there is no growth, prosperity and progress without the use of work private banker.